Control strategy of a cross-phase-connected unified power quality conditioner - Li, G.; Ma, F.; Choi, San Shing; Zhang, X. (The Institution of Engineering and Technology, 2012)
A three-phase unified power quality conditioner (UPQC) with cross-phase connection is investigated. The UPQC is designed to mitigate voltage sags/swells, including those resulting from single-phase faults. Based on an analysis of the configuration of the conditioner, multi-loop control schemes are proposed for the voltage and current compensation strategies. The practicability of the topology and the effectiveness of the control schemes are verified through simulations using PSCAD/EMTDC. The results demonstrate the proposed control strategy for the cross-phase-connected UPQC is capable of regulating load terminal voltage and compensating load current changes simultaneously and effectively. © 2012 The Institution of Engineering and Technology.